The Influence of Social Media Marketing Features on Purchase Decisions in Education Services - Muhammad Nur Irfan Wahyudi; Noor Suroija; Paniya, Paniya (Cita konsultindo, 2025)
The present research examines the impact of various social media marketing features, including interactivity, entertainment, perceived relevance, and informativeness, on consumer purchasing decisions in the educational service sector. The present study is anchored in the theoretical framework of consumer behaviour theory. A quantitative research design was employed, utilising a structured questionnaire administered to 100 high school students who actively utilise social media and have participated in educational programmes at the Brain Academy Centre in Semarang. Multiple linear regression analysis was performed using SPSS software. The findings suggest that perceived relevance (β = 0.220, p = 0.027) and informativeness (β = 0.280, p = 0.001) exert a statistically significant positive influence on purchase decisions, accounting for 44.6% of the variance (R² = 0.446). Conversely, interactivity and entertainment did not demonstrate significant effects. These findings contribute to the extant literature on social media marketing for intangible services and emphasise the practical importance of aligning content with consumers' informational needs. It is recommended that future research extend this analysis across a range of other social media platforms and demographic groups. This would allow for the validation and expansion of the insights derived from this analysis.